Pengembangan Perilaku Asertif dengan Teknik Sosiodrama untuk Mencegah Perilaku Bullying - Susilo Rahardjo; Edris Zamroni; Sumarni Sumarni; Derta Prihastuti (Universitas Mathla'ul Anwar Banten, 2020)
DEVELOPING ASSERTIVE BEHAVIOR WITH SOCIODRAMA TECHNIQUES TO PREVENT BULLYING BEHAVIOR. The influence of mass media has an impact on the spread of bullying behavior including in the school environment. The negative impact of student bullying becomes depressed, performance decreases, and can ultimately lead to students dropping out of school. Therefore it needs to be prevented so that it does not expand, and the school becomes a friendly and pleasant environment. The purpose of this research is to provide students with an understanding of bullying behavior that can occur at school, and students can prevent it by behaving assertively. One way to prevent bullying is to develop assertive student behavior. Through PTBK students are trained to prevent bullying behavior with the guidance of sociodrama techniques. The reader can develop a model of preventing bullying behavior in the same way or in other ways, so that the school becomes a pleasant and friendly environment.